Dashboards para desenvolvimento de aplicações e visualização de dados para plataformas de cidades inteligentes - Rolim, Douglas Arthur de Abreu (2020)
Smart city applications are inherently characterized by the integration of data from heterogeneous sources and the need of considering geographical information that represents the real-world urban space. To address these concerns, some platforms have been proposed in recent years offering common services and facilities to ease the development of smart city applications. Nonetheless, the existing platforms do not offer high-level interfaces to provide developers with proper tools that could reduce the complexity of developing applications, neither an interface to organize data visualization to end-users. Aiming at tackling such limitations, this work presents Web-based dashboards to support development and data visualization in smart city applications: the former is tailored to application developers, whereas the latter is suited to visualize data. This research: (i) proposes an architecture for the smart city platform interface that considers georeferenced data; (ii) implements such architecture in the context of Smart Geo Layers (SGeoL) middleware, including specific dashboard interfaces for application developers and users interested in applications built using the platform; (iii) discuss how the dashboards defined in this work are used in real applications, in the SGeoL context, which is a platform that combines georeferenced data, adresses interoperability and heterogeneity problems, and it is currently used in the context of the city of Natal. A controlled experiment with users was performed aimed to assess the benefits brought by the proposed dashboards in terms of application development effort and usability.